2000
DOI: 10.1017/s146114570000211x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the opioid system in the development and expression of sensitization to the locomotor-activating effect of ethanol

Abstract: Previous studies have shown that pretreatment with naloxone (Nlx), an opiate antagonist, attenuates the stimulating effect of ethanol. The purpose of the present study was to determine the influence of Nlx on the development and expression of the sensitization to ethanol. Initially, effects of different doses of Nlx on the response to a low dose of ethanol (2.0 g/kg) were assessed. Nlx (1.0 and 3.0 mg/kg i.p.) decreased the stimulating effect of ethanol. Groups of mice were treated with saline or Nlx (1.0 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 25 publications
6
40
0
1
Order By: Relevance
“…The role of specific subtypes of the mu opioid receptor (ie mu 1 + 2 or mu 3 ) in ethanol sensitization, however, appears to be limited; as we found that the functional relevance of these subtypes is restricted to the acute locomotor effects of ethanol. Data demonstrated robust sensitization to the locomotor activating effects of ethanol, as has previously been reported for Swiss mice (Camarini et al, 2000b;Miquel et al, 2003). Ethanol (2.5 g/kg) produced a significant increase in locomotor activity when acutely administered.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The role of specific subtypes of the mu opioid receptor (ie mu 1 + 2 or mu 3 ) in ethanol sensitization, however, appears to be limited; as we found that the functional relevance of these subtypes is restricted to the acute locomotor effects of ethanol. Data demonstrated robust sensitization to the locomotor activating effects of ethanol, as has previously been reported for Swiss mice (Camarini et al, 2000b;Miquel et al, 2003). Ethanol (2.5 g/kg) produced a significant increase in locomotor activity when acutely administered.…”
Section: Discussionsupporting
confidence: 79%
“…Male Swiss (IOPS Orl) albino mice, a strain chosen for its sensitivity to the stimulatory and sensitizing effects of ethanol (Camarini et al, 2000b;Miquel et al, 2003), were purchased from Janvier Spain, SA (Barcelona, Spain), housed (three per cage) and acclimated to the colony room for at least 2 weeks prior to study initiation. At the time of testing, mice were 6 weeks old.…”
Section: Subjects and Housingmentioning
confidence: 99%
See 3 more Smart Citations